Pengaruh Ukuran Perusahaan dan Leverage Terhadap Profitabilitas yang Dimoderasi oleh Kinerja Lingkungan - Asif, Ibnu; Pramono, Hadi; Wibowo, Hardiyanto; Dirgantari, Novi (E-Jurnal Akuntansi; Vol 35 No 1 (2025), 2025)
Climate change caused by mining company operational activities can have a negative impact on the surrounding community. The purpose of this study is to determine the effect of company size and leverage on profitability, with environmental performance as a moderating variable. This research method uses a quantitative method with a sample of mining companies listed on the IDX during 2020–2023. This study found a positive relationship between company size and profitability, but leverage had a negative impact on profitability. Environmental performance as a moderator was unable to moderate the relationship between company size and profitability, but environmental performance could weaken the relationship between leverage and profitability. Keywords: Company Size; Leverage; Profitability; Environmental Performance.